Native agarose gel electrophoresis and electroelution: a fast and cost-effective method to separate the small and large hepatitis B capsids - Yoon, Kam Yee; Tan, Wen Siang; Tey, Beng Ti; Lee, Khai Wooi; Ho, Kok Lian (Wiley-VCH Verlag, 2013)
Hepatitis B core antigen (HBcAg) expressed in Escherichia coli is able to self-assemble into large and small capsids comprising 240 (triangulation number T = 4) and 180 (triangulation number T = 3) subunits, respectively. Conventionally, sucrose density gradient ultracentrifugation and SEC have been used to separate these capsids. However, good separation of the large and small particles with these methods is never achieved. In the present study, we employed a simple, fast, and cost-effective method to separate the T = 3 and T = 4 HBcAg capsids by using native agarose gel electrophoresis followed by an electroelution method (NAGE-EE). This is a direct, fast, and economic method for isolating the large and small HBcAg particles homogenously based on the hydrodynamic radius of the spherical particles. Dynamic light scattering analysis demonstrated that the T = 3 and T = 4 HBcAg capsids prepared using the NAGE-EE method are monodisperse with polydispersity values of ∼15% and ∼13%, respectively. ELISA proved that the antigenicity of the capsids was not affected in the purification process. Overall, NAGE-EE produced T = 3 and T = 4 capsids with a purity above 90%, and the recovery was 34% and 50%, respectively (total recovery of HBcAg is ∼84%), and the operation time is 15 and 4 times lesser than that of the sucrose density gradient ultracentrifugation and SEC, respectively.